(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The Study of performance of rural cooperativecredit institutions has become essential. An asset becomes non-performing whennot to generate income for a financial institution. A non-performing asset doesnot give any return it incurs a cost by eating into earning made by bank. Themain problem of non-performing assets lies in the quality of managing creditrisk by the institutions. At present evaluate the non-performing asset positionin central or rural cooperative bank in Ambala. Non-performing Asset are causedas a result of various internal or external factors. What is various preventivemeasure and appraisal responsibility? Bank should monitor loans to identify andhaving potential to become not performing. The article aims to identifydifferent streams of thought that could guide future research.